Optimalisasi kapasitas tenaga kesehatan dan non kesehatan dalam pelayanan kesehatan di Rumah Sakit Prince Nayef, Banda Aceh, Indonesia (Optimalization of the health and non-health workerss capacity in health services at Prince Nayef Hospital, Banda Aceh, Indonesia) - Mayasari, Putri; Abdat, Munifah; Rachmah, R (Universitas Syiah Kuala, 2022)
This service aims to optimize the capacity of health and non-health workers in health services at Prince Nayef Hospital in Aceh, Indonesia. This activity was carried out for 2 days for material presentation on October 13-15 and continued with the evaluation stage from November 2021 - January 2022. This activity began with the preparation of proposals and the implementation of activities directly fulfilling health protocols and coordinating using communication media for 7 days. The activities carried out are providing socialization and strengthening of materials and skills related to service excellence in terms of effective communication and updating of information related to optimal services in hospitals. The next stage is a simulation on different days, as well as scheduled and continuous assistance with the implementation of activities. Followed by mentoring activities and evaluation of its application in each room during the handover. The results obtained, with the optimization activities with resource persons who are experts in their fields, have increased the knowledge of participants who take part in this service activity. In addition, there is an increase in awareness and motivation of Prince Nayef Hospital staff in the challenges of optimal health care. In conclusion, this activity provides benefits, namely making it easier for staff to gain access to increasing knowledge and information so that they can provide optimal service at Prince Nayef Hospital.